A multitechnique approach to probe the interaction of a therapeutic tyrosine kinase inhibitor nintedanib and bovine serum albumin. Issue 7 (9th August 2017) - Abdelhameed, Ali Saber; Nusrat, Saima; Paliwal, Sanjhi; Zaman, Masihuz; Zaidi, Nida; Khan, Rizwan Hasan
ABSTRACT: Drug and protein interaction provides a structural guideline in the rational drug designing and in the synthesis of new and improved drugs with greater efficacy. We have examined here the interaction tendency and mechanism of nintedanib (NTB), an anticancer drug (tyrosine kinase inhibitor) with bovine serum albumin (BSA), by spectroscopic techniques. The decline in Stern–Volmer quenching constants and binding constant with the temperature rise suggests that BSA forms a complex with NTB. Binding constant obtained by modified Stern–Volmer equation at 3 temperatures was realized to be of the order of 10 4 M −1 . Negative Δ G ( −5.93 kcal mol −1 ), Δ H (−3.74 kcal mol −1 ), and Δ S (−1.50 kcal mol −1 ) values exhibited a spontaneous and exothermic reaction between BSA and NTB. NTB molecule interacts with BSA by forming hydrogen bonds, as elucidated by fluorescence results. Moreover, a minor increment in the helical conformation of BSA upon its binding to NTB was observed by circular dichroism spectroscopy. The modification in protein's symmetry and a decline in hydrodynamic radii were observed in the presence of NTB (from 3.6 to 3 nm) as obtained by the dynamic light scattering measurement results. GRAPHICAL ABSTRACT: